Penilaian Sustainable Supply Chain Management Dengan Metode Life Cycle Assessment (Studi Kasus: Produk Tepung Bumbu, PT XYZ) - Moch. Annas Hidayatulloh; Ernawati, Dira; Dewi, Sinta (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Industrialization in Indonesia contributes significantly to increased emissions. PT XYZ as a seasoning producer faces challenges in managing the environmental impact of its supply chain activities, especially in seasoning flour products which have the highest productivity reaching 25,793 tons in 2023. This study aims to measure the level of emissions generated during the supply chain process of seasoning flour products using the Life Cycle Assessment (LCA) method with a gate to gate approach. Data collection was carried out through interviews and secondary data collection from company documents related to process procedures, energy consumption, raw material usage, and supply chain operational data. Data was processed using SimaPro 9.0 software with the ReCiPe 2016 Midpoint method. The results showed a high level of emissions. The terrestrial acidification category reached 4.97 kg.SO₂, far above the standard limit of 600 mg.SO₂ per year. Normalization results identified the production stage as the largest contributor with three categories of marine ecotoxicity (27.3), freshwater ecotoxicity (17.5), and human carcinogenic toxicity (13.5). The high emissions are caused by significant electricity consumption for operational systems and production machinery, as well as transportation use. Recommendations for improvement include optimizing production energy, managing machine operating time, utilizing solar panels, and others.